(untitled) (Biological Sciences - PJSIR, 2022)
Magur (Clarias batrachus) fry were reared for a period of twelve days in plastic bowl to determine the effect of different feeds (live plankton, frozen plankton, dried plankton and Tubifex) on survival rate and growth. Survival was found to be comparatively higher with live Tubifex and live plankton. Greatest length (13.0 mm) was obtained with Tubifex and least (11.0 mm) with dried plankton.